Pengaruh Beban Iklan, Harga Transfer Dan Volatilitas Harga Saham Terhadap Agresivitas Pajak Dengan Ukuran Perusahaan Sebagai Variabel Moderasi - Alisya Athalia; Nera Marinda Machdar (Manajemen Kreatif Jurnal, 2024)
Tax aggressiveness is an effort to reduce the tax burden, either by means that comply with the law or that violate the law. This research investigates the relationship between Advertising Expenses, Transfer Prices, Stock Price Volatility on Tax Aggressiveness and Company Size as a Moderating Variable. This research applies descriptive statistical analysis with a quantitative-based approach. The research results show that advertising expenses have a negative influence on tax aggressiveness, while transfer prices and share price volatility have a positive influence on tax aggressiveness. And company size strengthens the influence of transfer prices on tax aggressiveness. Company size weakens the influence of advertising expenses and share price volatility on tax aggressiveness.